2018
DOI: 10.3390/nu10101421
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gluten-Free Diet on Health and the Gut Microbiota Cannot Be Extrapolated from One Population to Others

Abstract: Gluten-related disorders (GRD) affect millions of people worldwide and have been related to the composition and metabolism of the gut microbiota. These disorders present differently in each patient and the only treatment available is a strict life-long gluten-free diet (GFD). Several studies have investigated the effect of a GFD on the gut microbiota of patients afflicted with GRD as well as healthy people. The purpose of this review is to persuade the biomedical community to think that, while useful, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 103 publications
(96 reference statements)
1
26
0
Order By: Relevance
“…This study has limitations that are relevant to future studies. First, this and other studies lack a large enough sample size to generalize phenomena and even with bigger samples sizes the results cannot be extrapolated from one population to others [ 17 ]. Second, gluten-free diets vary widely around the world and these may or may not lead to a microbial state more similar to healthy controls [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has limitations that are relevant to future studies. First, this and other studies lack a large enough sample size to generalize phenomena and even with bigger samples sizes the results cannot be extrapolated from one population to others [ 17 ]. Second, gluten-free diets vary widely around the world and these may or may not lead to a microbial state more similar to healthy controls [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that the gut microbiota is closely related to GRDs, particularly CD [ 8 , 12 ]; however, a disease-specific microbial signature of GRDs has not yet been defined and there is a lack of consensus with respect to the specific changes involved in these disorders with or without dietary gluten [ 12 , 13 , 14 , 15 ], partly due to the well-known high interindividual variation of the gut microbiota [ 16 , 17 ]. One study used culture techniques to investigate the effect of GFD on fecal Bifidobacterium and showed that CD patients have a lower load of this microorganism [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes seen may be because gluten or fructans exert a prebiotic action, with their exclusion provoking change in gut microbial composition . However, caution should be taken when interpreting these findings, as individuals have highly unique microbiota, and findings may not be able to be extrapolated from one population to another .…”
Section: Gluten‐free Dietmentioning
confidence: 99%
“…Despite this, recent RCTs suggest that a low-FODMAPs diet can further reduce the severity of depressive symptoms in those with NCGS [ 29 ] and CD [ 78 ] already on a GFD, although further research is needed in this area. In addition, while it has been suggested that altered gut microbiota may contribute to the psychiatric effects of a GFD [ 29 , 79 , 80 ], results should not be extrapolated from one population to another, due to the highly individualised pattern of gut microbial composition [ 81 ]. In any case, future studies should be mindful of the shortcomings of only considering mean scores of the sample as a whole, and closer attention should be paid to patients who may be unresponsive to a GFD in research and practice.…”
Section: Discussionmentioning
confidence: 99%